Asuhan Keperawatan Anak Pada Pasien Dengan Bronkopneumonia Di Ruang Anak Rsud Prof. H. Muhammad Yamin, S.HPariaman Tahun 2026 - Tia Rahmadani; Prima Yoselina; Reska Handayani; Yessy Aprihatin (CV. ITTC INDONESIA, 2026)
Bronchopneumonia is a lung infection that commonly occurs in children under 5 years old which causes inflammation of the bronchioles (small airways and alveoli air sacs in the lungs). The purpose of this study is to describe the application of nursing care to pediatric patients with bronchopneumonia. This method uses a case study conducted for 5 days on (8–12 February 2026) in the pediatric ward of Prof. Muhammad Yamin SH. Pariaman Regional Hospital. After the assessment was completed, 4 nursing diagnoses were found, namely ineffective airway clearance, ineffective breathing pattern, hyperthermia, and nutritional deficit. The implementation of nursing provided aims to monitor general conditions and vital signs, teach semi-Fowler's position to facilitate breathing, monitor respiratory status, provide warm compresses, and educate about fulfilling nutritional needs to the family. After 5 days of treatment, the patient's condition showed improvement, marked by improved breathing patterns, decreased body temperature and increased family understanding of nutritional needs being met. The results of this case study emphasize the importance of the role of parents in supporting the child's healing process, especially in recognizing early signs of shortness of breath and Parents should be able to respond quickly and appropriately if their child is short of breath. With proper knowledge and preparedness, parents can play an active role in ensuring their child's safety and health.